Review of the Oriental genus Platysodes Westwood (Coleoptera: Scarabaeidae: Cetoniinae: Cremastocheilini) with a redescription of Platysodes madoni Bourgoin - Qiu, Jian-Yue; Xu, Hao; Chen, Li (Zootaxa, 2015)
The genus Platysodes Westwood, 1873 (Coleoptera: Scarabaeidae: Cetoniinae: Cremastocheilini) is reviewed, with an identification key, images, and distributional map for all species. Platysodes madoni Bourgoin, 1923 is newly recorded from southern China, and a lectotype is designated for this species. The year of publication of Platysodes is corrected to 1873.